2020
DOI: 10.1002/btm2.10189
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐microbubble cavitation facilitates adeno‐associated virus mediated cochlear gene transfection across the round‐window membrane

Abstract: The round window of the cochlea provides an ideal route for delivering medicines and gene therapy reagents that can cross the round window membrane (RWM) into the inner ear. Recombinant adeno-associated viruses (rAAVs) have several advantages and are recommended as viral vectors for gene transfection. However, rAAVs cannot cross an intact RWM. Consequently, ultrasound-mediated microbubble (USMB) cavitation is potentially useful, because it can sonoporate the cell membranes, and increase their permeability to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…This is the first study to reveal that the middle and upper third areas of the RWM exhibit the strongest response to cavitation. Furthermore, the size of the affected area accounts for approximately one-quarter of the whole RWM, in agreement with a recent study conducted in guinea pigs that indicated that the damaged region was focused in the one-third area located anteriorly on the RWM (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is the first study to reveal that the middle and upper third areas of the RWM exhibit the strongest response to cavitation. Furthermore, the size of the affected area accounts for approximately one-quarter of the whole RWM, in agreement with a recent study conducted in guinea pigs that indicated that the damaged region was focused in the one-third area located anteriorly on the RWM (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…be 0.207 MI, and applied it in the mouse model. The resultant ultrastructural changes in the outer epithelium were evidently less severe compared with previous US damage observed in a guinea pig model (Lin et al, 2019;Zhang et al, 2021). The physical explanation for this discrepancy lies in the fact that, at the same high frequency of 1 MHz, increases in the sound pressure at certain ranges achieve a higher cavitation activity or strength-the so-called cavitation intensity (Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations